Choosing the lesser evil: The rationality and limits of the failing firm defense - Segovia Trocones, Enzo Pierino (2020)
On May 11, 2020, during the health and economic crisis caused by COVID-19, Legislative Decree 1510 was issued, which made a few amendments to various rules on free and fair competition. One of the amendments provided that the Law on Merger Control added, as a criterion to be considered for the procedures for assessing a merger, the financial crisis of one of the companies concerned and the need to carry out the merger duly accredited by the notifying parties. In this paper, the author observes that the fact that one of the companies is undergoing financial difficulties is not sufficient to allow for flexibility in the merger control. To demonstrate this, he presents a brief description of the failing firm defense from a historical perspective, the most relevant precedents in the United States and the European Union, and the current requirements for its accreditation in those jurisdictions and in Latin American countries. Finally, he presents the economic, industrial and social rationality underlying this exception and the possibilities of being applied in Peruvian practice.